Iron-rich phase iron-manganese system P3 type sodium ion battery positive electrode material, preparation method and battery

By adopting the positive electrode material of the iron-rich iron-manganese-based P3-type sodium ion battery, the multi-dopation and element stacking effects are used to solve the problems of insufficient structural stability, air stability and circulation capacity of existing materials, and the effects of high capacity, long circulation and high stability are achieved.

CN119764436APending Publication Date: 2025-04-04NAYUAN NEW MATERIAL TECH (WUXI) CO LTD

Patent Information

Application Number
CN202411763736.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have problems with insufficient structural stability, air stability and circulation capacity. In particular, the O3-phase nickel ferromanganese 111 material is prone to precipitation of iron elements when circulating at high voltage, resulting in poor circulation capacity.

Method used

The positive electrode material of the iron-rich iron-manganese-based P3-type sodium ion battery is adopted. Through multi-doping and element stacking effects, the structural stability and air stability of the material are improved, and the charging and discharge capacity and long circulation capacity are guaranteed under a higher voltage range.

Benefits of technology

The effects of high capacity, long cycle and high stability are achieved. The made sodium ion battery has a high specific capacity and a long cycle life, overcoming the problems of insufficient stability and circulation capacity of traditional materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764436A_ABST
    Figure CN119764436A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-rich phase iron-manganese system P3 type sodium ion battery positive electrode material, a preparation method and a battery. The general formula of a sodium transition metal oxide of the positive electrode material is Na < x > Fe Mn M < c > Nd < LeO < 2 >, wherein x is larger than 0.7 and smaller than or equal to 0.9, a is larger than or equal to 0.7 and larger than or equal to 0.3, b is larger than or equal to 0.6 and larger than or equal to 0.3, c is larger than or equal to 0.2 and larger than 0, d is larger than or equal to 0.1 and larger than 0, e is larger than or equal to 0.1 and larger than 0, a + b + c + d + e = 1, M is one of Li and K, and N and L are two different elements of Ni, Mg, Al, B, La, Zn, Ti, Ca, Zr and Cu. The positive electrode material provided by the embodiment of the invention takes an iron-rich P3 phase as a main phase, compared with a traditional O3-phase ferro-nickel-manganese 111 positive electrode material (sodium = 1.0), the structural stability and air stability of the material are improved, the charge-discharge capacity and long-cycle capacity of the material are ensured in a relatively high voltage interval (2-4.3 V), and compared with a traditional P2-phase ferro-manganese positive electrode material, the material has the advantages that the material is stable in performance, and the service life of the material is prolonged. The positive electrode material disclosed by the invention has the effects of high capacity, high stability and long circulation, and the prepared sodium ion battery has relatively high specific capacity and relatively long circulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of sodium ion batteries, and in particular to an iron-rich iron-manganese-based P3 type sodium ion battery positive electrode material, a method for preparing the iron-rich iron-manganese-based P3 type sodium ion battery positive electrode material, and a sodium ion battery. Background Art

[0002] Layered transition metal oxide cathode materials for sodium ion batteries use sodium sources as raw materials. Compared with lithium battery materials, they are low-cost and easy to process. Due to their excellent electrochemical properties and wide range of raw material sources, they are considered to be one of the most promising cathode materials for sodium ion batteries. However, the known layered materials are mainly nickel-iron-manganese systems, and nickel is used as the main material, which makes their raw material costs relatively high. For systems that do not contain nickel (such as iron-manganese systems), the synthesized material capacity is relatively low due to the lack of nickel's high-voltage redox contribution.

[0003] The research on iron-manganese materials is mainly focused on O3 phase nickel-iron-manganese 111. The O3 phase nickel-iron-manganese 111 material has a higher charge-discharge specific capacity due to its higher sodium content (Na=1.0), but its structural stability and air stability are extremely poor. At the same time, due to the overflow of iron elements under high voltage, the O3 phase 111 series material has poor cycle stability, which is not conducive to large-scale promotion and application. Summary of the invention

[0004] The present application provides an iron-rich iron-manganese-based P3-type sodium ion battery positive electrode material, a preparation method and a sodium ion battery. The iron-manganese-based positive electrode material is a P3-phase transition metal oxide layered structure with an iron-rich P3 phase as the main phase. Compared with the traditional O3-phase nickel-iron-manganese 111 positive electrode material (sodium = 1.0), the material of the present application adopts multi-element doping and element stacking effects to obtain a special P3-phase material configuration, which increases the structural stability and air stability of the material; in a higher voltage range (2-4.3V), the charge and discharge capacity and long cycle capacity of the material are guaranteed; the positive electrode material of the present application has the effects of high capacity, high stability and long cycle, and the prepared sodium ion battery has a higher specific capacity and a longer cycle.

[0005] In the first aspect, the present application provides an iron-rich phase iron-manganese system P3 type sodium ion battery positive electrode material, the general formula of the sodium transition metal oxide of the positive electrode material is Na x Fe a Mn b M c N d L e O 2; Among them, 0.7<x≤0.9, 0.7≥a≥0.3, 0.6≥b≥0.3, 0.2≥c>0, 0.1≥d>0, 0.1≥e>0, a+b+c+d+e=1, M is one of Li and K, and N and L are two different elements among Ni, Mg, Al, B, La, Zn, Ti, Ca, Zr, and Cu.

[0006] In a second aspect, the present application provides a method for preparing an iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material, comprising the following steps:

[0007] According to the stoichiometric ratio, an iron salt and a manganese salt are mixed and dissolved in water to obtain a corresponding first transition metal salt aqueous solution, and the obtained first transition metal salt aqueous solution is precipitated by a coprecipitation method, the pH value is controlled, and a first transition metal hydroxide precipitation precursor is obtained after spray drying;

[0008] According to the stoichiometric ratio, the sodium-containing compound, the first transition metal hydroxide precipitation precursor, and the M-containing compound, the N-containing compound, and the L-containing compound are mixed, ball-milled, tableted, and sintered to obtain the iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material.

[0009] In a third aspect, the present application provides another method for preparing an iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material, comprising the following steps:

[0010] According to the stoichiometric ratio, the sodium-containing compound, the iron-containing compound, the manganese-containing compound, the M-containing compound, the N-containing compound and the L-containing compound are mixed, ball-milled, refined, tableted and sintered to obtain the iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material.

[0011] In a fourth aspect, the present application provides a sodium ion battery, comprising a positive electrode material, wherein the positive electrode material comprises the iron-rich iron-manganese P3 type sodium ion battery positive electrode material as described in the first aspect above, or comprises the iron-rich iron-manganese P3 type sodium ion battery positive electrode material prepared by the preparation method of the iron-rich iron-manganese P3 type sodium ion battery positive electrode material as described in the second aspect or the third aspect above.

[0012] The technical effects of this application are:

[0013] Compared with the prior art, the iron-rich iron-manganese P3 type sodium ion battery positive electrode material provided in the embodiment of the present application combines the advantages of traditional P2 phase transition metal oxides and O3 phase transition metal oxides. The traditional P2 phase iron-manganese positive electrode material (Na≤0.67) often leads to low material capacity due to its own insufficient sodium content and insufficient redox active sites, that is, there is not enough sodium or enough redox sites for deintercalation, so that the overall capacity is low when the full battery is assembled (the specific capacity is generally ≤80mAh / g); and the traditional O3 phase iron-manganese positive electrode material (Na=1.0), although it has a higher sodium content, so that the material has a higher charge and discharge specific capacity, but due to its relatively fragile interlayer structure and excessively high sodium content, its structural stability and air stability are poor, and it is easy to cause the precipitation of iron elements when circulating under high voltage (4.3V), resulting in poor cycling ability; and the present application The material has a relatively high sodium content (Na content is between 0.7 and 0.9) and is an iron-rich P3 phase (Fe≥0.3), which solves the problem of low specific capacity of traditional P2 phase iron-manganese positive electrode materials and improves the charge and discharge capacity of the material (the material of this application achieves discharge in a higher voltage range (2-4.3V), with a specific capacity of ≈140mAh / g); and solves the problems of poor air stability and poor circulation of traditional O3 phase nickel-iron-manganese 111 materials; at the same time, this material adopts a multi-doping strategy, and while introducing a cationic disordered element (Li, K), it also introduces two synergistic doping elements (Zr, Mg, Ni, Ca, La, Al, Ti, etc.). The introduction of two synergistic doping elements can greatly enhance the stability of the material framework structure; and the introduction of cationic disordered elements and lower valence synergistic elements also ensures the possibility of introducing more sodium ions (Na≥0.7).

[0014] The iron-rich P3 phase iron-manganese materials (Fe≥0.3) have both the good structural stability and air stability of the P phase materials and the high charge-discharge specific capacity of the O3 phase materials. They have great potential for realizing the characteristics of high specific capacity, high stability and high capacity of iron-manganese positive electrode materials. The research on related P3 phase iron-manganese materials is of great strategic significance for further reducing the overall cost of sodium electricity and improving the overall performance of existing sodium-ion batteries. Specifically, the design of the iron-rich phase (Fe≥0.3) changes the Fe / Mn ratio, making the material more inclined to form the P3 phase while obtaining more redox active sites, ensuring the high sodium content and structural stability of the material; at the same time, the synergistic doping of multiple doping elements and the stacked structural model greatly enhance the stability of the material's framework structure, allowing sodium ions to be better deintercalated. During the charge and discharge process, due to the sufficient redox active sites provided by the iron-rich phase design, while Fe provides abundant redox active sites, the redox of Mn is suppressed, reducing the Tyler distortion of the Mn element as a structural support point, making the overall structure less damaged during the sodium ion insertion and extraction process, so that the material of the present application has the characteristics of high capacity, long cycle, high stability, etc.

[0015] The preparation method of the iron-rich phase iron-manganese system P3 type sodium ion battery positive electrode material provided in the embodiment of the present application adopts the method of coprecipitation combined with calcination, or adopts mixing, ball milling, refinement, tableting, sintering treatment to obtain, and has the characteristics of cheap raw materials, easy to obtain, simple preparation process, etc., and the obtained iron-rich phase iron-manganese system P3 type sodium ion battery positive electrode material has complete crystal form and high purity. In a specific implementation, by adjusting the sodium content and the main element ratio of iron and manganese, especially controlling the sodium content within an appropriate range (0.75≤Na≤0.85), increasing the proportion of iron elements (constructing an iron-rich phase) and introducing more elements with lower cation potential energy such as lithium, potassium, nickel, and magnesium, by regulating the overall cation potential energy, a relatively pure phase P3 type structure sodium ion battery positive electrode material can be effectively synthesized, so that the P3 phase purity in the prepared positive electrode material is higher, so that the structural stability, air stability, charge and discharge capacity and long cycle capacity of the positive electrode material can be further increased. At the same time, during the synthesis process, by adjusting the airflow (air / oxygen ratio) and controlling the gas flow rate, the sintering atmosphere is maintained in a relatively high gas intake concentration range, which can further effectively sinter out a relatively pure iron-rich iron-manganese-based P3 type sodium ion battery positive electrode material.

[0016] The sodium ion battery provided in the embodiment of the present application provides a higher gram capacity and better structural stability for the sodium ion battery of the present application due to the use of an iron-rich phase iron-manganese system P3 type sodium ion battery positive electrode material as the positive electrode material; relative to the traditional P2 material, the material of the present application ensures a high capacity with high sodium and sufficient redox active sites; relative to the traditional O3 phase nickel-iron-manganese 111 material, the material of the present application adopts multi-element doping and element stacking effects to improve the structural stability and air stability of the material; and in a higher voltage range (2-4.3V), the iron element will participate in the redox process, and the multi-element doping simultaneously inhibits the precipitation of iron during the charge and discharge process, and also inhibits the redox of Mn, reducing the Jan-Taylor distortion of the Mn element as a structural support point, so that the material stability is further enhanced, and the long cycle capacity of the material is increased; the positive electrode material of the present application has the effects of high capacity, high stability, and long cycle, and the prepared sodium ion battery has a higher specific capacity and a longer cycle.

[0017] In order to more clearly demonstrate the technical means of the present application and ensure the smooth implementation of the contents of the specification, some typical embodiments of the present application are listed below together with drawings and detailed descriptions. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 XRD patterns of the iron-rich phase iron-manganese P3-type sodium transition metal oxide (Fe≥0.3) prepared in Examples 1 to 6 of the present application, the nickel-iron-manganese O3-type sodium transition metal oxide prepared in Comparative Example 1, and the iron-manganese P2-type sodium transition metal oxide prepared in Comparative Example 2;

[0019] Figure 2 This is a SEM image of the iron-rich iron-manganese-based P3 type sodium ion battery positive electrode material prepared in Example 1 of the present application;

[0020] Figure 3 A schematic diagram of the first cycle charge and discharge curve of a sodium ion half-cell assembled from materials of an iron-rich phase iron-manganese-based P3-type sodium transition metal oxide in Example 1 of the present application at 2.0 to 4.3 V and 0.1 C;

[0021] Figure 4 A schematic diagram of a long cycle of a sodium ion half-cell assembled with the materials of Example 1 of the present application at 2.0-4.3V and 0.5C;

[0022] Figure 5 XRD spectra of the iron-rich iron-manganese P3-type sodium transition metal oxide (Fe≥0.3) prepared in Example 1 of the present application and the nickel-iron-manganese O3-type sodium transition metal oxide in Comparative Example 1, both original and after standing in air for one month. DETAILED DESCRIPTION

[0023] In order to make the invention purpose and technical solution of the present application clearer and easier to understand, the content of the present application is further described in detail below in conjunction with the accompanying drawings and examples. However, it should be clear that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application. Without departing from the spirit and substance of the present application, modifications and replacements made to the method, preparation steps or conditions of the present application are within the scope of the present application.

[0024] The present application provides an iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material. The sodium transition metal oxide of the positive electrode material has the following general formula:

[0025] Na x Fe a Mn b M c N d L e O 2 ;

[0026] Among them, 0.7<x≤0.9, 0.7≥a≥0.3, 0.6≥b≥0.3, 0.2≥c>0, 0.1≥d>0, 0.1≥e>0, a+b+c+d+e=1, M is one of Li and K, and N and L are two different elements among Ni, Mg, Al, B, La, Zn, Ti, Ca, Zr, and Cu.

[0027] For example: x is 0.71, 0.8, 0.9, etc.; a is 0.3, 0.4, 0.5, 0.6, 0.7, etc.; b is 0.3, 0.4, 0.5, 0.6, etc.; c is 0.05, 0.1, 0.15, 0.2, etc.; d is 0.25, 0.05, 0.1, etc.; e is 0.25, 0.05, 0.1, etc.

[0028] In the embodiment of the present application, the iron-rich iron-manganese-based P3 type sodium ion battery positive electrode material refers to a sodium ion battery positive electrode material whose main phase is the P3 phase. It should be noted that the sodium ion battery positive electrode material whose main phase is the P3 phase can be a pure P3 phase sodium ion battery positive electrode material, and can also be a mixed phase sodium ion battery positive electrode material, that is, a sodium ion battery positive electrode material whose main phase is the P3 phase but also contains the P2 phase and / or the O3 phase, etc., which is not specifically limited here.

[0029] The iron-manganese positive electrode material prepared in the embodiment of the present application has the iron-rich P3 phase as the main phase, adopts multi-element doping and element stacking effects, and controls the value ranges of multiple elements to make the prepared iron-manganese positive electrode material a P3 phase transition metal oxide layered structure. Compared with the traditional O3 phase nickel-iron-manganese 111 positive electrode material (sodium = 1.0), the structural stability and air stability of the material are increased; in a higher voltage range (2-4.3V), the charge and discharge capacity and long cycle capacity of the material are guaranteed; compared with the traditional P2 phase iron-manganese positive electrode material, the capacity of the positive electrode material is increased, the charge and discharge capacity of the positive electrode material is improved, and the sodium ion battery prepared using the positive electrode material has a higher specific capacity and a longer cycle.

[0030] In some embodiments, 0.75≤x≤0.85, 0.55≥a≥0.3, 0.5≥b≥0.35, 0.15≥c>0, for example: x is 0.75, 0.8, 0.85, etc.; a is 0.3, 0.4, 0.5, 0.55, etc.; b is 0.4, 0.45, 0.5, etc.; c is 0.05, 0.1, 0.15, etc.

[0031] The iron-manganese cathode material prepared in the embodiment of the present application can control the sodium content within an appropriate range (0.75≤Na≤0.85), increase the proportion of iron elements (construct an iron-rich phase), and introduce more elements with lower cation potential energy such as lithium, potassium, nickel, and magnesium. Thus, by adjusting the content of sodium, iron, and other elements, the overall cation potential energy can be regulated, which is conducive to synthesizing a purer phase P3-type structure sodium ion battery cathode material, so that the P3 phase purity in the prepared cathode material is higher, thereby further increasing the structural stability, air stability, charge and discharge capacity, and long cycle capacity of the cathode material.

[0032] In some embodiments, the sodium transition metal oxide may be Na 0.75 Fe 0.4 Mn 0.4 Li 0.1 Zr 0.05 La 0.0 5 O 2 、Na 0.8 Fe 0.55 Mn 0.35 Li 0.05 Zn 0.025 Cu 0.025 O 2 、Na 0.8 Fe 0.3 Mn 0.5 Li 0.05 Ni 0.05 Al 0.05 O 2 、Na0.75 Fe 0.3 Mn 0. 5 K 0.1 B 0.05 Ca 0.05 O 2 , Na 0.85 Fe 0.35 Mn 0.45 Li 0.15 Mg 0.025 Ti 0.025 O 2 , Na 0.85 Fe 0.5 Mn 0.35 K 0.1 Mg 0.025 Ti 0.025 O 2 , very little in the middle.

[0033] Like Figure 1 indication, Figure 1 This is Na 0.75 Fe 0.4 Mn 0.4 Li 0.1 Zr 0.05 La 0.05 O 2 , Na 0.8 Fe 0.55 Mn 0.35 Li 0.05 Zinc 0.02 5 Cu 0.025 O 2 , Na 0.8 Fe 0.3 Mn 0.5 Li 0.05 Ni 0.05 Al 0.05 O 2 , Na 0.75 Fe 0.3 Mn 0.5 K 0.1 B 0.05 Ca 0.05 O 2 , Na 0.85 Fe 0.35 Mn 0.45 Li 0.15 Mg 0.025 Ti 0.025 O 2 , Na 0.85 Fe 0.5 Mn 0.35 K 0.1 Mg 0.025 Ti0.025 O 2 , for example, the XRD (X-ray diffraction) spectrum, the horizontal axis is twice the incident angle of the x-ray (θ) (2θ, the unit is degree), and the vertical axis is the intensity after diffraction (intensity, au in the figure is the abbreviation of absorbance unit); according to Figure 1 It can be seen that this type of sodium transition metal oxide has a P3 phase transition metal oxide layered structure and has a high sodium content. While maintaining a high capacity, it also maintains excellent structural stability.

[0034] In some embodiments, the main phase of the positive electrode material is a P3 phase, and further contains at least one of a P2 phase transition metal oxide and an O3 phase transition metal oxide.

[0035] It should be noted that the main phase of the positive electrode material prepared in the embodiment of the present application is the P3 phase, and it may also contain a P2 phase transition metal oxide or an O3 phase transition metal oxide, etc. For example, the positive electrode material may contain a P3 phase transition metal oxide and a P2 phase transition metal oxide, or may contain a P3 phase transition metal oxide and an O3 phase transition metal oxide, or may contain a P3 phase transition metal oxide, a P2 phase transition metal oxide and an O3 phase transition metal oxide at the same time, and no specific limitation is made here. Preferably, the iron-manganese positive electrode material prepared in the embodiment of the present application contains only the P3 phase, thereby making the P3 phase in the prepared positive electrode material higher in purity, thereby further increasing the structural stability, air stability, charge and discharge capacity and long cycle capacity of the positive electrode material.

[0036] The present application provides a method for preparing the above-mentioned iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material, which comprises the following steps:

[0037] According to the stoichiometric ratio, an iron salt and a manganese salt are mixed and dissolved in water to obtain a corresponding first transition metal salt aqueous solution, and the obtained first transition metal salt aqueous solution is precipitated by a coprecipitation method, the pH value is controlled, and a first transition metal hydroxide precipitation precursor is obtained after spray drying;

[0038] According to the stoichiometric ratio, the sodium-containing compound, the first transition metal hydroxide precipitation precursor, and the M-containing compound, the N-containing compound, and the L-containing compound are mixed, ball-milled, tableted, and sintered to obtain the iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material.

[0039] The embodiment of the present application provides another method for preparing the above-mentioned iron-rich phase iron-manganese based P3 type sodium ion battery positive electrode material, which comprises the following steps: mixing, ball milling, refining, tableting, and sintering sodium-containing compounds, iron-containing compounds, manganese-containing compounds, M-containing compounds, N-containing compounds, and L-containing compounds according to a stoichiometric ratio to obtain the iron-rich phase iron-manganese based P3 type sodium ion battery positive electrode material.

[0040] The preparation method is explained in detail below.

[0041] According to the stoichiometric ratio, an iron salt and a manganese salt are mixed and dissolved in water to obtain a corresponding first transition metal salt aqueous solution, the first transition metal salt aqueous solution is precipitated by a coprecipitation method, the pH value is controlled, and a first transition metal hydroxide precipitation precursor is obtained after spray drying; according to the stoichiometric ratio, a sodium-containing compound, the first transition metal hydroxide precipitation precursor, and an M-containing compound, an N-containing compound, and an L-containing compound are mixed, ball-milled, tableted, and sintered to obtain the iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material.

[0042] In some embodiments, the feeding ratio of the iron salt and the manganese salt for the co-precipitation reaction is (0.5-1):(0.5-1).

[0043] In some embodiments, the sodium-containing compound is at least one of sodium carbonate, sodium acetate, and sodium hydroxide. The iron salt is at least one of iron sulfate, iron nitrate, iron chloride, and iron acetate; the manganese salt is at least one of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate; before the coprecipitation reaction, it is necessary to prepare the iron salt and the manganese salt into corresponding aqueous solutions to improve the reaction efficiency of the coprecipitation reaction.

[0044] In some embodiments, when performing the coprecipitation reaction, a precipitant needs to be added to the solution to adjust the pH value of the reaction system. In some embodiments, the precipitant used can be a mixed solution of sodium hydroxide and ammonia water.

[0045] In some embodiments, the molar ratio of sodium in the sodium-containing compound: the first transition metal hydroxide precipitation precursor: M, N, L in the M-containing compound, the N-containing compound, and the L-containing compound is (0.7-0.9): (0.7-1.0): (0-0.3), followed by ball milling, tableting, and sintering.

[0046] Alternatively, in some embodiments, sodium-containing compounds, iron-containing compounds, manganese-containing compounds, and M-containing compounds, N-containing compounds, and L-containing compounds are mixed, ball-milled, refined, tableted, and sintered according to a stoichiometric ratio to obtain the iron-rich iron-manganese-based P3 sodium ion battery positive electrode material.

[0047] In some embodiments, according to the molar ratio, the sodium in the sodium-containing compound: the iron in the iron-containing compound: the manganese in the manganese-containing compound: the M, N, and L in the M-containing compound, the N-containing compound, and the L-containing compound are (0.7-0.9): (0.3-0.7): (0.3-0.6): (0-0.3).

[0048] In some embodiments, the iron-containing compound is at least one of ferrous oxide, ferric oxide, ferric hydroxide, ferric carbonate, and ferrous oxalate; the manganese-containing compound is at least one of manganous oxide, manganese dioxide, manganese hydroxide, manganese carbonate, and manganese oxalate; the sodium-containing compound is at least one of sodium carbonate, sodium acetate, and sodium hydroxide.

[0049] The M-containing compound is at least one of an M-containing metal oxide, an M-containing oxide, an M-containing carbonate, and an M-containing hydroxide; the N-containing compound is at least one of an N-containing metal oxide, an N-containing oxide, an N-containing carbonate, and an N-containing hydroxide; and the L-containing compound is at least one of an L-containing metal oxide, an L-containing oxide, an L-containing carbonate, and an L-containing hydroxide.

[0050] In some embodiments, when the sodium-containing compound is mixed with the first transition metal hydroxide precipitation precursor and the M-containing compound, the N-containing compound, and the L-containing compound, or when the sodium-containing compound, the iron-containing compound, the manganese-containing compound, and the M-containing compound, the N-containing compound, and the L-containing compound are mixed, mechanical grinding can be adopted, or they can be made into a solution, mixed and ultrasonically shaken to form a slurry, and then dried, ball milled, etc. The purpose of mixing is to make the sodium-containing compound and the first transition metal hydroxide precipitation precursor and the M-containing compound, the N-containing compound, and the L-containing compound mixed evenly, or to make the sodium-containing compound, the iron-containing compound, the manganese-containing compound, and the M-containing compound, the N-containing compound, and the L-containing compound mixed evenly, so as to facilitate sintering into an iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material.

[0051] In some embodiments, the sintering conditions are first sintering at a constant temperature of 400-550° C. for 1-5 hours, then heating to 800-1100° C. and sintering at a constant temperature for 10-24 hours, and the sintering atmosphere is oxygen or air or a mixture of oxygen and air.

[0052] The preparation method of the iron-rich phase iron-manganese system P3 type sodium ion battery positive electrode material provided in the embodiment of the present application adopts the method of coprecipitation combined with calcination, or adopts mixing, ball milling, refinement, tableting, sintering treatment to obtain, and has the characteristics of cheap and easy-to-obtain raw materials and simple preparation process. The obtained iron-rich phase iron-manganese system P3 type sodium ion battery positive electrode material has complete crystal form and high purity. At the same time, during the synthesis process, by adjusting the airflow (air / oxygen ratio) and controlling the airflow size, the sintering atmosphere is kept in a range of higher air intake concentration, and a relatively pure iron-rich phase iron-manganese system P3 type sodium ion battery positive electrode material can be effectively sintered, which is beneficial to improve the P3 phase purity of the positive electrode material.

[0053] The sodium ion battery provided by the embodiment of the present application, due to the use of iron-rich phase iron-manganese system P3 type sodium ion battery positive electrode material as the positive electrode material, provides a higher gram capacity and better structural stability for the sodium ion battery of the present application; relative to the traditional P2 phase material, the present material solves the problem of insufficient redox active sites leading to low capacity, while improving the charge and discharge capacity of the material, at a higher voltage range (2-4.3V), the energy density of the material is increased; relative to the traditional O3 phase material, the material of the present application adopts the P3 phase design, and the multi-element doping and element stacking effect increase the stability of the material layer, and improve the structural stability and air stability of the material; during the charge and discharge process, due to the sufficient redox active sites provided by the iron-rich phase design, while Fe provides abundant redox active sites, the redox of Mn is suppressed, and the Mn element is reduced as the structural support point of the Jiang Taylor distortion, so that the material stability is further enhanced. The positive electrode material of the present application has the effects of high capacity, high stability and long cycle, and the prepared sodium ion battery has a higher specific capacity and a longer cycle.

[0054] Therefore, the embodiments of the present application also provide a positive electrode sheet and a sodium ion battery using the above-mentioned iron-rich phase iron-manganese based P3 type sodium ion battery positive electrode material.

[0055] Among them, the positive electrode sheet uses an iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material as the positive electrode active material, and also contains a conductive agent and a binder.

[0056] Specifically, the iron-rich phase iron-manganese system P3 type sodium ion battery positive electrode material is mixed with a conductive agent, a binder and a solvent to form a positive electrode slurry, which is coated on the surface of the positive electrode collector, and then dried, rolled and cut into pieces to form a positive electrode sheet. The mass ratio of the iron-rich phase iron-manganese system P3 type sodium ion battery positive electrode material, the conductive agent and the binder in the positive electrode sheet is 8:1:1. When preparing the positive electrode slurry, the solvent can be N-methylpyrrolidone (NMP).

[0057] The sodium ion battery includes the above-mentioned positive electrode sheet, or the positive electrode material contains the iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material of the embodiment of the present application.

[0058] In some embodiments, the positive electrode material of the sodium ion battery of the embodiment of the present application, in addition to the iron-rich phase iron-manganese based P3 type sodium ion battery positive electrode material of the present application, may also contain at least one of a P2 phase structured positive electrode material and an O3 phase positive electrode material.

[0059] In some embodiments, the sodium ion battery provided in the embodiments of the present application uses metallic sodium as the negative electrode material, and the electrolyte is any one of 1M NaPF6 / (EC:DMC=1:1) electrolyte, 1M NaPF6 / PC electrolyte, and 1M NaClO4 / (EC:PC=1:1) electrolyte, wherein EC represents ethylene carbonate, DMC represents dimethyl carbonate, PC represents propylene carbonate, EC:DMC=1:1 represents a solvent formed by ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, and EC:PC represents a solvent formed by ethylene carbonate and propylene carbonate in a volume ratio of 1:1.

[0060] In some embodiments, the sodium ion battery provided in the embodiments of the present application uses a diaphragm that is a polyolefin microporous membrane such as polyethylene, polypropylene, etc., such as a Celgard diaphragm.

[0061] Example 1

[0062] A method for preparing an iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material comprises the following steps:

[0063] (a) iron sulfate and manganese sulfate are mixed and dissolved in water at a molar ratio of 4:4 to prepare a 1.0 mol / L mixed transition metal salt solution, a mixed aqueous solution of 1.0 mol / L sodium hydroxide and 0.10 mol / L ammonia water is used as a precipitant, the pH value is controlled to be about 8-10, and an iron-manganese hydroxide precursor is prepared by coprecipitation, and the obtained precursor is spray-dried to obtain a powder.

[0064] (b) Sodium carbonate, the hydroxide precursor powder obtained in step (a), lithium carbonate, zirconium oxide and lanthanum oxide are mixed in a molar ratio of 0.375:0.8:0.05:0.05:0.025 and added into a ball mill together with grinding beads of the same weight, and ball milled at a speed of 200 r / min for 2 h. The mixed powder is taken out and mixed evenly in a mortar.

[0065] (c) The powder mixed in step (b) was pressed into a disc with a diameter of 20 mm on a cold press at a pressure of 100 MPa for 5 min.

[0066] (d) The pressed flake mixture in step (c) was placed in a tube furnace, heated to 500°C in a mixed atmosphere of oxygen and air (mixing ratio 2:8) and sintered at a constant temperature for 2 h, then heated to 900°C and sintered at a constant temperature for 20 h, and naturally cooled to room temperature to obtain sample 1, whose molecular formula is Na 0.75 Fe 0.4 Mn 0.4 Li 0.1 Zr 0.05 La 0.05 O 2 .

[0067] The obtained sample 1 was subjected to XRD and SEM (Scanning Electron Microscope) tests. The specific test results are shown in Figure 1 and Figure 2 , the cycle performance is shown in Table 1.

[0068] Example 2

[0069] According to the molar ratio, sodium carbonate, ferrous oxalate, manganese dioxide, lithium carbonate, zinc oxide and copper oxide are mixed in a molar ratio of 0.4:0.55:0.35:0.025:0.025:0.025, and added to a ball mill together with grinding beads of the same weight, and part of ethanol is added at the same time, and high-energy ball milling is carried out at a speed of 300r / min for 8h, and the mixed powder is taken out and dried, mixed in a mortar, and then referred to the treatment method (c)-(d) in Example 1, after tableting and sintering, an iron-rich phase iron-manganese system P3 type sodium ion battery positive electrode material Na is obtained. 0.8 Fe 0.55 Mn 0.35 Li 0.05 Zn 0.025 Cu 0.025 O 2 , its XRD spectrum is as follows Figure 1 The cycle performance is shown in Table 1.

[0070] Example 3

[0071] Referring to Example 1, ferrous sulfate and manganese sulfate were prepared in a molar ratio of 3:5 to prepare a hydroxide precursor, sodium carbonate, the prepared hydroxide precursor and lithium carbonate, nickel hydroxide, and aluminum oxide were mixed in a molar ratio of 0.4:0.8:0.025:0.05:0.025, and then the treatment method (b)-(d) in Example 1 was followed to obtain an iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material Na 0.8 Fe 0.3 Mn 0.5 Li 0.05 Ni 0.05 Al0.05 O 2 , its XRD spectrum is as follows Figure 1 The cycle performance is shown in Table 1.

[0072] Example 4

[0073] Referring to Example 1, ferrous sulfate and manganese sulfate were prepared in a molar ratio of 3:5 to prepare a hydroxide precursor, sodium carbonate, the prepared hydroxide precursor and potassium carbonate, boron oxide, and calcium oxide were mixed in a molar ratio of 0.375:0.8:0.05:0.025:0.05, and then the treatment method (b)-(d) in Example 1 was followed to obtain an iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material Na 0.75 Fe 0.3 Mn 0.5 K 0.1 B 0.05 Ca 0.05 O 2 , its XRD spectrum is as follows Figure 1 The cycle performance is shown in Table 1.

[0074] Example 5

[0075] Referring to Example 1, ferrous sulfate and manganese sulfate were prepared in a molar ratio of 3.5:4.5 to prepare a hydroxide precursor, sodium carbonate, the prepared hydroxide precursor and lithium carbonate, magnesium oxide, and titanium oxide were mixed in a molar ratio of 0.425:0.8:0.075:0.025:0.025, and then the treatment method (b)-(d) in Example 1 was followed to obtain an iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material Na 0.85 Fe 0.35 Mn 0.45 Li 0.15 Mg 0.025 Ti 0.025 O 2 , its XRD spectrum is as follows Figure 1 The cycle performance is shown in Table 1.

[0076] Example 6

[0077] Referring to Example 1, ferrous sulfate and manganese sulfate were prepared in a molar ratio of 5:3.5 to prepare a hydroxide precursor, sodium carbonate, the prepared hydroxide precursor and potassium carbonate, magnesium oxide, and titanium oxide were mixed in a molar ratio of 0.425:0.85:0.05:0.025:0.025, and then the treatment method (b)-(d) in Example 1 was followed to obtain an iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material Na 0.85 Fe 0.5 Mn 0.35 K 0.1Mg 0.025 Ti 0.025 O 2 , its XRD spectrum is as follows Figure 1 The cycle performance is shown in Table 1.

[0078] Comparative Example 1

[0079] A nickel-iron-manganese O3 type sodium layered sodium transition metal oxide positive electrode material:

[0080] (a) nickel sulfate, iron sulfate and manganese sulfate are mixed and dissolved in water at a molar ratio of 1:1:1 to prepare a 1.0 mol / L mixed transition metal salt solution of nickel sulfate and manganese sulfate, a mixed aqueous solution of 1.0 mol / L sodium carbonate and 0.10 mol / L ammonia water is used as a precipitant, and the pH value is controlled to be about 8.0;

[0081] Preparation of nickel-iron-manganese hydroxide precursor by coprecipitation.

[0082] (b) Sodium carbonate and the hydroxide precursor obtained in step (a) are mixed in a molar ratio of 0.5:1 and added into a ball mill and ball milling balls, and ball milled at a speed of 200 r / min for 2 h. The mixed powder is taken out and mixed evenly in a mortar.

[0083] (c) The uniformly mixed precursor powders were pressed into discs with a diameter of 20 mm on a cold press at a pressure of 100 MPa for 5 min.

[0084] (d) The sheet precursor pressed in step (c) was placed in a tube furnace, heated to 500° C. and sintered at a constant temperature for 2 h in a mixed atmosphere of oxygen and air (mixing ratio 2:8), then heated to 900° C. and sintered at a constant temperature for 20 h, and naturally cooled to room temperature to obtain a comparative example sample Na 1.0 Ni 0.33 Fe 0.33 Mn 0.33 O 2 , its XRD spectrum is as follows Figure 1 shown.

[0085] Comparative Example 2

[0086] An iron-poor phase iron-manganese system multi-element doped P2-type layered sodium transition metal oxide positive electrode material:

[0087] (a) Iron sulfate and manganese sulfate are mixed and dissolved in water at a molar ratio of 2:8 to prepare a 1.0 mol / L mixed transition metal salt solution of nickel sulfate and manganese sulfate, and a mixed aqueous solution of 1.0 mol / L sodium carbonate and 0.10 mol / L ammonia water is used as a precipitant, and the pH value is controlled to be about 8.0 to prepare an iron manganese hydroxide precursor by co-precipitation.

[0088] (b) Sodium carbonate and the hydroxide precursor obtained in step (a) were mixed at a molar ratio of 0.335:1 and added into a ball mill and ball milling balls, and ball milled at a speed of 200 r / min for 2 h. The mixed powders were taken out and mixed evenly in a mortar.

[0089] (c) The uniformly mixed precursor powders were pressed into discs with a diameter of 20 mm on a cold press at a pressure of 100 MPa for 5 min.

[0090] (d) The sheet precursor pressed in step (c) was placed in a tube furnace, heated to 500° C. and sintered at a constant temperature for 2 h in a mixed atmosphere of oxygen and air (mixing ratio 2:8), then heated to 900° C. and sintered at a constant temperature for 20 h, and naturally cooled to room temperature to obtain a comparative example sample Na 0.67 Fe 0.2 Mn 0.8 O 2 , its XRD spectrum is as follows Figure 1 shown.

[0091] Application Example 1

[0092] A sodium ion battery, the preparation method of which comprises the following steps:

[0093] (1) The sample obtained in Example 1 was used as a positive electrode active material, mixed with conductive carbon black and polyvinylidene fluoride (PVDF) binder in a mass ratio of 8:1:1, dissolved in N-methylpyrrolidone (NMP) solvent to prepare a positive electrode slurry, and coated on an aluminum foil, dried, and cut to obtain a positive electrode sheet.

[0094] (2) The positive electrode obtained in step (1) was assembled with metal sodium and Celgard separator into a sodium ion battery, wherein the electrolyte of the sodium ion battery was a mixture of 1M NaPF6 / (EC:DMC=1:1) (according to the volume ratio of EC:DMC=1:1). After assembly, the battery was allowed to stand for 24 hours, and then subjected to charge and discharge activation test.

[0095] Specifically, the test method is: charge and discharge three times at a current density of 0.1C (1C = 100 mA / g) within a voltage range of 2.0-4.3V; and then perform a cycle performance test at 0.5C (1C = 100 mA / g). The results are shown in Table 1.

[0096] Application Example 2

[0097] A sodium ion battery, the preparation method of which comprises the following steps:

[0098] (1) The sample obtained in Example 2 was used as a positive electrode active material, mixed with conductive carbon black and polyvinylidene fluoride (PVDF) binder in a mass ratio of 8:1:1, dissolved in N-methylpyrrolidone (NMP) solvent to prepare a positive electrode slurry, and coated on an aluminum foil, dried, and cut to obtain a positive electrode sheet.

[0099] (2) The positive electrode obtained in step (1) was assembled with metal sodium and Celgard separator into a sodium ion battery, wherein the electrolyte of the sodium ion battery was a mixture of 1M NaPF6 / (EC:DMC=1:1) (according to the volume ratio of EC:DMC=1:1). After assembly, the battery was allowed to stand for 24 hours, and then subjected to charge and discharge activation test.

[0100] Specifically, the test method is: charge and discharge three times at a current density of 0.1C (1C = 100 mA / g) within a voltage range of 2.0-4.3V; and then perform a cycle performance test at 0.5C (1C = 100 mA / g). The results are shown in Table 1.

[0101] Application Example 3

[0102] A sodium ion battery, the preparation method of which comprises the following steps:

[0103] (1) The sample obtained in Example 3 was used as a positive electrode active material, mixed with conductive carbon black and polyvinylidene fluoride (PVDF) binder in a mass ratio of 8:1:1, dissolved in N-methylpyrrolidone (NMP) solvent to prepare a positive electrode slurry, and coated on an aluminum foil, dried, and cut to obtain a positive electrode sheet.

[0104] (2) The positive electrode obtained in step (1) was assembled with metal sodium and Celgard separator into a sodium ion battery, wherein the electrolyte of the sodium ion battery was a mixture of 1M NaPF6 / (EC:DMC=1:1) (according to the volume ratio of EC:DMC=1:1). After assembly, the battery was allowed to stand for 24 hours, and then subjected to charge and discharge activation test.

[0105] Specifically, the test method is: charge and discharge three times at a current density of 0.1C (1C = 100 mA / g) within a voltage range of 2.0-4.3V; and then perform a cycle performance test at 0.5C (1C = 100 mA / g). The results are shown in Table 1.

[0106] Application Example 4

[0107] A sodium ion battery, the preparation method of which comprises the following steps:

[0108] (1) The sample obtained in Example 4 was used as a positive electrode active material, mixed with conductive carbon black and polyvinylidene fluoride (PVDF) binder in a mass ratio of 8:1:1, dissolved in N-methylpyrrolidone (NMP) solvent to prepare a positive electrode slurry, and coated on an aluminum foil, dried, and cut to obtain a positive electrode sheet.

[0109] (2) The positive electrode obtained in step (1) was assembled with metal sodium and Celgard separator into a sodium ion battery, wherein the electrolyte of the sodium ion battery was a mixture of 1M NaPF6 / (EC:DMC=1:1) (according to the volume ratio of EC:DMC=1:1). After assembly, the battery was allowed to stand for 24 hours, and then subjected to charge and discharge activation test.

[0110] Specifically, the test method is: charge and discharge three times at a current density of 0.1C (1C = 100 mA / g) within a voltage range of 2.0-4.3V; and then perform a cycle performance test at 0.5C (1C = 100 mA / g). The results are shown in Table 1.

[0111] Application Example 5

[0112] A sodium ion battery, the preparation method of which comprises the following steps:

[0113] (1) The sample obtained in Example 5 was used as a positive electrode active material, mixed with conductive carbon black and polyvinylidene fluoride (PVDF) binder in a mass ratio of 8:1:1, dissolved in N-methylpyrrolidone (NMP) solvent to prepare a positive electrode slurry, and coated on an aluminum foil, dried, and cut to obtain a positive electrode sheet.

[0114] (2) The positive electrode obtained in step (1) was assembled with metal sodium and Celgard separator into a sodium ion battery, wherein the electrolyte of the sodium ion battery was a mixture of 1M NaPF6 / (EC:DMC=1:1) (according to the volume ratio of EC:DMC=1:1). After assembly, the battery was allowed to stand for 24 hours, and then subjected to charge and discharge activation test.

[0115] Specifically, the test method is: charge and discharge three times at a current density of 0.1C (1C = 100 mA / g) within a voltage range of 2.0-4.3V; and then perform a cycle performance test at 0.5C (1C = 100 mA / g). The results are shown in Table 1.

[0116] Application Example 6

[0117] A sodium ion battery, the preparation method of which comprises the following steps:

[0118] (1) The sample obtained in Example 6 was used as a positive electrode active material, mixed with conductive carbon black and polyvinylidene fluoride (PVDF) binder in a mass ratio of 8:1:1, dissolved in N-methylpyrrolidone (NMP) solvent to prepare a positive electrode slurry, and coated on an aluminum foil, dried, and cut to obtain a positive electrode sheet.

[0119] (2) The positive electrode obtained in step (1) was assembled with metal sodium and Celgard separator into a sodium ion battery, wherein the electrolyte of the sodium ion battery was a mixture of 1M NaPF6 / (EC:DMC=1:1) (according to the volume ratio of EC:DMC=1:1). After assembly, the battery was allowed to stand for 24 hours, and then subjected to charge and discharge activation test.

[0120] Specifically, the test method is: charge and discharge three times at a current density of 0.1C (1C = 100 mA / g) within a voltage range of 2.0-4.3V; and then perform a cycle performance test at 0.5C (1C = 100 mA / g). The results are shown in Table 1.

[0121] Application Example 7

[0122] A sodium ion battery, the preparation method of which comprises the following steps:

[0123] (1) The sample obtained in Comparative Example 1 was used as a positive electrode active material, mixed with conductive carbon black and polyvinylidene fluoride (PVDF) binder in a mass ratio of 8:1:1, dissolved in N-methylpyrrolidone (NMP) solvent to prepare a positive electrode slurry, and coated on an aluminum foil, dried, and cut to obtain a positive electrode sheet.

[0124] (2) The positive electrode obtained in step (1) was assembled with metal sodium and Celgard separator into a sodium ion battery, wherein the electrolyte of the sodium ion battery was a mixture of 1M NaPF6 / (EC:DMC=1:1) (according to the volume ratio of EC:DMC=1:1). After assembly, the battery was allowed to stand for 24 hours, and then subjected to charge and discharge activation test.

[0125] Specifically, the test method is: charge and discharge three times at a current density of 0.1C (1C = 100 mA / g) within a voltage range of 2.0-4.3V; and then perform a cycle performance test at 0.5C (1C = 100 mA / g). The results are shown in Table 1.

[0126] Application Example 8

[0127] A sodium ion battery, the preparation method of which comprises the following steps:

[0128] (1) The sample obtained in Comparative Example 2 was used as a positive electrode active material, mixed with conductive carbon black and polyvinylidene fluoride (PVDF) binder in a mass ratio of 8:1:1, dissolved in N-methylpyrrolidone (NMP) solvent to prepare a positive electrode slurry, and coated on an aluminum foil, dried, and cut to obtain a positive electrode sheet.

[0129] (2) The positive electrode obtained in step (1) was assembled with metal sodium and Celgard separator into a sodium ion battery, wherein the electrolyte of the sodium ion battery was a mixture of 1M NaPF6 / (EC:DMC=1:1) (according to the volume ratio of EC:DMC=1:1). After assembly, the battery was allowed to stand for 24 hours, and then subjected to charge and discharge activation test.

[0130] Specifically, the test method is: charge and discharge three times at a current density of 0.1C (1C = 100 mA / g) within a voltage range of 2.0-4.3V; and then perform a cycle performance test at 0.5C (1C = 100 mA / g). The results are shown in Table 1.

[0131] Figure 1 The main diffraction peaks of all samples from Example 1 to Example 6 show a P3 type structure, and the sodium content is Na=0.75-0.85, the crystal form is complete and the impurity content is low, proving that the obtained material is a P3 type high sodium iron-manganese multinary doped sodium transition metal oxide positive electrode material:

[0132] Na 0.75 Fe 0.4 Mn 0.4 Li 0.1 Zr 0.05 La 0.05 O 2 、Na 0.8 Fe 0.55 Mn 0.35 Li 0.05 Zn 0.025 Cu 0.025 O 2 、Na 0.8 Fe 0.3 Mn 0.5 Li 0.05 Ni 0.05 Al 0.05 O 2 、Na 0.75 Fe 0.3 Mn 0.5 K 0.1 B 0.05 Ca 0.05 O 2 、Na 0.85 Fe 0.35 Mn 0.45 Li 0.15Mg 0.025 Ti 0.02 5 O 2 、Na 0.85 Fe 0.5 Mn 0.35 K 0.1 Mg 0.025 Ti 0.025 O 2 ;

[0133] At the same time, Comparative Examples 1 and 2 also show standard O3 and P2 crystal structures (wherein the significant O3 peak type is marked by an asterisk, and has a certain peak position difference with the P3 peak type).

[0134] from Figure 2 It can be seen from the SEM that sample 1 of Example 1 has a lamellar structure. Please note that Figure 2 The dimension in the lower right corner is 20 μm.

[0135] The iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material Na obtained in Example 1 0.75 Fe 0.4 Mn 0.4 Li 0.1 Zr 0.05 La 0.05 O 2 As the positive electrode material, they were assembled into sodium ion batteries with sodium metal negative electrode and the electrochemical performance was tested. Figure 3 As shown, the sodium ion battery assembled by the sample of Example 1 has a reversible initial capacity of about 137 mAh / g when cycled at a current density of 0.1C (10 mA / g) in the voltage range of 2.0 to 4.3 V. The reason is that Example 1 in the present application introduces a higher iron content, and the sufficient abundance of iron elements provides sufficient redox active sites. In the higher voltage range (2-4.3 V), the iron element will participate in the redox process, greatly enhancing the deintercalation ability of Na ions, thereby improving the characteristic gram capacity. At the same time, in the subsequent long cycle test, such as Figure 4 As shown, when cycled at 0.5C (50mA / g), the material of Example 1 still retains a discharge specific capacity of about 112mAh / g, and after 100 long cycles, the capacity retention rate is still about 90%. Figure 5The stability of Example 1 and Comparative Example 1 under air is demonstrated. From the XRD results, it can be found that the iron-rich phase iron-manganese system P3 type sodium ion battery positive electrode material in the present application does not decompose after standing in the air for one month, while the XRD peak of the ordinary O3 type nickel-iron-manganese 111 sodium ion battery positive electrode material almost disappears after standing in the air for one month, and the material is completely decomposed. In the iron-rich P3 phase material of the present application, the introduction of electrochemical synergistic doping elements (Li, K, Ni, Mg, Ca, La, Al, Ti and other elements) inhibits the precipitation of iron during the charge and discharge process under high pressure, and also inhibits the oxidation and reduction of Mn, reduces the T-T distortion of the Mn element as a structural support point, greatly enhances the stability of the material framework structure and the air stability, and increases the long cycle capacity of the material; the material of Example 1 is stable in the air, and the structural changes during the electrochemical cycle are highly reversible, and has good long cycle performance.

[0136] In addition, Table 1 shows the materials of Examples 1-6, the charge and discharge capacity test results at 0.5C and the long cycle test results. The results show that Examples 1-6 all exhibit relatively high specific discharge capacity (110-130mAh / g), and the capacity retention rates after 100 cycles are close to or exceed 90%, all showing excellent cycle performance. In comparison, although the material of Comparative Example 1 still shows a relatively high initial discharge capacity (116mAh / g), the cycle performance is poor (capacity retention rate after 100 cycles is 67%) due to phase changes during cycling at high voltage. Although Comparative Example 2 has excellent cycle stability, its effective charge and discharge capacity is relatively low (≤90mAh / g). Therefore, the iron-rich phase iron-manganese based P3 type sodium ion battery positive electrode material of the embodiment of the present application overcomes the problems of poor air stability and poor cycle under high voltage of the traditional O3 phase nickel-iron-manganese 111 material, and the problem of low capacity of the traditional P2 phase iron-manganese material. The material of the embodiment of the present application has good cycle stability, structural stability and air stability; at the same time, the material is mainly iron-manganese based material with extremely low element cost, which provides a solution for developing new categories of low-cost sodium ion batteries.

[0137] Table 1

[0138]

[0139] It should be understood that the terms used in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application.

[0140] It should also be understood that the term “and / or” used in the specification and appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0141] The above is only a specific embodiment of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. An iron-rich phase iron-manganese system P3 type sodium ion battery positive electrode material, characterized in that: The sodium transition metal oxide of the positive electrode material has the general formula shown below: And x Fe a Mn b I c N d L e O2; Among them, 0.7<x≤0.9, 0.7≥a≥0.3, 0.6≥b≥0.3, 0.2≥c>0, 0.1≥d>0, 0.1≥e>0, a+b+c+d+e=1, M is any one of Li and K, and N and L are two different elements of Ni, Mg, Al, B, La, Zn, Ti, Ca, Zr, and Cu.

2. The positive electrode material according to claim 1, characterized in that 0.75≤x≤0.85, 0.55≥a≥0.3, 0.5≥b≥0.35, 0.15≥c>0.

3. The positive electrode material according to claim 2, characterized in that The sodium transition metal oxide is Na 0.75 Fe 0.4 Mn 0. 4Li 0.1 Zr 0.05 La 0.05 O2、Na 0.8 Fe 0.55 Mn 0.35 Li 0.05 Zn 0.025 Cu 0.025 O2、Na 0.8 Fe 0.3 Mn 0.5 Li 0.05 Ni 0.05 Al 0.05 O2、Na 0.75 Fe 0.3 Mn 0.5 K 0.1 B 0.05 Ca 0.05 O2、Na 0.85 Fe 0.35 Mn 0.45 Li 0.15 Mg 0.025 Ti 0.025 O2、Na 0.85 Fe 0.5 Mn 0.35 K 0.1 Mg 0.025 Ti 0.025 O2, at least one of.

4. The positive electrode material according to any one of claims 1 to 3, characterized in that The main phase of the positive electrode material is P3 phase, and it also contains at least one of P2 phase transition metal oxide and O3 phase transition metal oxide.

5. A method for preparing the iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: According to the stoichiometric ratio, an iron salt and a manganese salt are mixed and dissolved in water to obtain a corresponding first transition metal salt aqueous solution, the first transition metal salt aqueous solution is precipitated by a coprecipitation method, the pH value is controlled, and a first transition metal hydroxide precipitation precursor is obtained after spray drying; according to the stoichiometric ratio, a sodium-containing compound, the first transition metal hydroxide precipitation precursor, and an M-containing compound, an N-containing compound, and an L-containing compound are mixed, ball-milled, tableted, and sintered to obtain the iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material.

6. The preparation method according to claim 5, wherein the ratio of the iron salt and the manganese salt for the coprecipitation reaction is (0.5-1):(0.5-1); Sodium in the sodium-containing compound: iron and manganese in the first transition metal hydroxide precipitation precursor: M, N, and L in the M-containing compound, the N-containing compound, and the L-containing compound = (0.7 to 0.9): (0.7 to 1.0): (0 to 0.3); The sintering conditions are: first sinter at a constant temperature of 400-550°C for 1-5 hours, then heat up to 800-1100°C and sinter at a constant temperature for 10-24 hours. The sintering atmosphere is oxygen or air or a mixture of oxygen and air.

7. The preparation method according to claim 5, characterized in that: The sodium-containing compound is at least one of sodium carbonate, sodium acetate and sodium hydroxide; The iron salt is at least one of ferric sulfate, ferric nitrate, ferric chloride and ferric acetate; The manganese salt is at least one of manganese sulfate, manganese nitrate, manganese chloride and manganese acetate; The M-containing compound is at least one of an M-containing metal oxide, an M-containing oxide, an M-containing carbonate, and an M-containing hydroxide; The N-containing compound is at least one of a N-containing metal oxide, a N-containing oxide, a N-containing carbonate, and a N-containing hydroxide; The L-containing compound is at least one of an L-containing metal oxide, an L-containing oxide, an L-containing carbonate, and an L-containing hydroxide.

8. A method for preparing the iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: According to the stoichiometric ratio, the sodium-containing compound, the iron-containing compound, the manganese-containing compound, the M-containing compound, the N-containing compound and the L-containing compound are mixed, ball-milled, refined, tableted and sintered to obtain the iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material.

9. The preparation method according to claim 8, characterized in that: According to the molar ratio, the sodium in the sodium-containing compound: the iron in the iron-containing compound: the manganese in the manganese-containing compound: the M, N, and L in the M-containing compound, the N-containing compound, and the L-containing compound are (0.7-0.9):(0.3-0.7):(0.3-0.6):(0-0.3); The sintering conditions are: first sintering at a constant temperature of 400-550°C for 1-5 hours, then heating to 800-1100°C and sintering at a constant temperature for 10-24 hours, and the sintering atmosphere is oxygen or air or a mixture of oxygen and air; The iron-containing compound is at least one of ferrous oxide, ferric oxide, ferric hydroxide, ferric carbonate, and ferric oxalate; The manganese-containing compound is at least one of manganese oxide, manganese dioxide, manganese hydroxide, manganese carbonate, and manganese oxalate; The sodium-containing compound is at least one of sodium carbonate, sodium acetate and sodium hydroxide; The M-containing compound is at least one of an M-containing metal oxide, an M-containing oxide, an M-containing carbonate, and an M-containing hydroxide; The N-containing compound is at least one of a N-containing metal oxide, a N-containing oxide, a N-containing carbonate, and a N-containing hydroxide; The L-containing compound is at least one of an L-containing metal oxide, an L-containing oxide, an L-containing carbonate, and an L-containing hydroxide.

10. A sodium ion battery, comprising a positive electrode material, characterized in that: The positive electrode material comprises the iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material according to any one of claims 1 to 4, or comprises the iron-rich phase iron-manganese-based P3 type sodium ion battery positive electrode material prepared by the preparation method according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • Sodium-ion battery positive electrode material with long cycle stability and high magnification

    CN115347182A

  • Double-site metal ion doped nickel iron sodium manganate positive electrode material and preparation method thereof, positive electrode plate and sodium ion battery

    CN118315567A

  • Multi-element doped iron-manganese series sodium ion battery positive electrode material, preparation method and battery

    CN118630198A

  • Method For Producing Sodium Composite Transition Metal Oxide, Positive Electrode Active Material For Sodium Secondary Battery, Positive Electrode And Sodium Secondary Battery Comprising The Same

    US20200119348A1

  • Layered sodium ion battery positive electrode material and preparation method therefor and use thereof

    WO2024174475A1

Cited By

  • Sodium battery precursor and preparation method thereof, sodium battery positive electrode material and sodium battery

    CN121627062A